“Film“ comme non-film – Samuel Beckett et le spectacle vivant de l’angoisse - CÂMPEAN, Noemina (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
Film as Not-Film – Samuel Beckett and the Vivid Show of Anxiety. This paper aims to offer a psychoanalytic reading of the living suffering of Samuel Beckett concerning the trauma of birth doubled by the sin of being born with particular reference to his theatrical work Film from 1965. In Film the real nothing is converted into the image of multiple eyes (“I”s) which, beyond the idea of tragedy, translates the multiple division of the subject into Eye and Object, an acting out of the self-consciousness through the concentric circles of the anxiety. In this sense, the theatrical play between in-between and out-between grasps anxiety as the symptom of every event of the real. With his (not)film, Beckett represents I and Eye, Not I and Not Eye at the same time.